Development of personnel motivation models as a key component of innovative activity management - D.O. Krykunenko (Marketing i Menedžment Innovacij, 2014)
The aim of the article. The aim of the article is to examine the algorithm, approaches and methods of development the model of staff motivation at high technology enterprises, to strengthen the creative-directed processes of developing new products, as well as analysis of additional factors that have contributed to the effective creative work of the staff. The results of the analysis. The problem of improving the efficiency of different economic systems in the situation of limited amount of resources and fierce competition among enterprises is highlighted in the article. The author found that the performance of the considered task can be achieved through the active use of creative abilities of employees. Entities of innovative business must address the development of management concepts creativity of staff motivation model of creative work, the development and application of a wide range of methods and instruments for the control creativity. In this case, the algorithm of motivation improvement involves defining the objective model of motivation, diagnosis of the existing system of staff incentives, building a creative ranking of employees, development of effective methods of creative work motivation. Scientific novelty of the present study is in organizing of staff creativity management, which involves the intensification and revitalization innovations of the company, the aim of which is in development and implementation of innovative products. An important phase of model motivation is to create additional motivators manifestation of the creative energy of employees, which will increase the cost-effectiveness of high-tech enterprises, to reduce the turnaround time for the development of innovative products. Thus, the development, implementation and operation of the motivation model to incorporate the creative abilities of the staff of the enterprise should be based on an integrated, generalized, systemic and integrated approach, taking into account the existing foreign and domestic experience, characteristics of the formation of all structural elements of incentive systems at the enterprise. It is established that continued efforts in research management creativity should be focused on developing the effective methodology for assessing the actual level of creativity and the development potential of the creative staff of high-tech enterprises. These indicators will show the effectiveness of the implementation of measures aimed at the use of creative abilities of employees. Conclusions and directions of further researches. Further researches should be concentrated at studying the ways to improve the effectiveness and improvement of the creativity of staff knowledge-based enterprises to strengthen and intensify the processes of innovation development of various businesses. The role of creativity in creation and implementation of innovative products is that it can have a significant impact on improving the functioning of economic systems. Practical implementation of the results will significantly increase the number of science-based innovation by enterprises, as well as reduce the time of execution of various kinds of design work, through the adoption of creative engineering and management decisions.